Beclin-1: a therapeutic target at the intersection of autophagy, immunotherapy, and cancer treatment - Cao, Zhumin; Tian, Ke; Ran, Yincheng; Zhou, Haonan; Zhou, Lei; Ding, Yana; Tang, Xiaowei (Frontiers in Immunology, 2024)
The significant identification of Beclin-1’s function in regulating autophagy flow signified a significant progression in our understanding of cellular operations. Beclin-1 acts as a scaffold for forming the PI3KC3 complex, controlling autophagy and cellular trafficking processes in a complicated way. This intricate protein has garnered considerable attention due to its substantial impact on the development of tumors. Strong evidence indicates Beclin-1 plays a critical role in controlling autophagy in various human cancer types and its intricate connection with apoptosis and ferroptosis. The potential of Beclin-1 as a viable target for cancer therapy is highlighted by its associations with key autophagy regulators such as AMPK, mTOR, and ATGs. Beclin-1 controls the growth and dissemination of tumors by autophagy. It also affects how tumors react to therapies such as chemotherapy and radiation therapy. The role of Beclin-1 in autophagy can influence apoptosis, depending on whether it supports cell survival or leads to cell death. Beclin-1 plays a crucial role in ferroptosis by increasing ATG5 levels, which in turn promotes autophagy-triggered ferroptosis. Finally, we analyzed the possible function of Beclin-1 in tumor immunology and drug sensitivity in cancers. In general, Beclin-1 has a significant impact on regulating autophagy, offering various potentials for medical intervention and altering our understanding of cancer biology.